Identification guide to some Diaptomid species (Crustacea, Copepoda, Calanoida, Diaptomidae) of "de la Plata" River Basin (South America) - Perbiche-Neves, Gilmar (2015)
An identification guide is presented for species of calanoid copepod family Diaptomidae from "de la Plata" River Basin (Argentina, Brazil, Bolivia, Paraguay and Uruguay). It was based on material collected during the summer and winter of 2010 from 43 sites across the eastern part and the lower stretches of this basin, the second largest in South America and the fourth in the world. The guide contains identification keys and species diagnoses for males and females, richly supported by scanning electronic micrographs and/or line drawings of 19 species. It also includes some general remarks on the taxonomy and phylogenetic relationships of these species. The key was adjusted to be useful for these species only, with separate keys for each sex, and is the first for females of South America. One species classified herein as incertae sedis was not included in the analysis. At least ten other species have previously been recorded in the basin but were not present in our samples. This is the first attempt to compile comprehensive taxonomic information on this group of copepods in this region, and it is expected to become a useful tool for biologists and young taxonomists interested in the crustacean biota of the Neotropical region.